Influence of Stent Flexibility on Artery Wall Stress and Wall Shear Stress in Bifurcation Lesions - Saito N (Dove Medical Press, 2020)
Noboru Saito, Yuhei Mori, Tomoya Komatsu Terumo Shonan Center, Kanagawa 259-0151, JapanCorrespondence: Noboru SaitoTerumo Shonan Center, 1500 Inokuchi, Nakai-Machi, Ashigarakami-Gun, Kanagawa 259-0151, JapanTel +81-465-81-4251Fax +81-465-81-4217Email noboru_saitou@terumo.co.jpPurpose: Stent flexibility can influence clinical outcome, especially in bifurcation lesions. For instance, an overly rigid stent can impose mechanical stress on the artery at the stent edges and alter both arterial geometry and blood flow dynamics in bifurcations. This study investigated the influence of stent flexibility on vessel geometry, histology, wall stress, and blood flow dynamics in arterial bifurcations.Materials and Methods: We compared arterial angulation, stenosis, histopathology, simulated wall shear stress (WSS), and simulated blood flow velocity distribution in swine coronary artery bifurcations following placement of the less flexible Multi-link 8 or more flexible Kaname stent (4.1 ± 0.5 vs 1.5 ± 0.1 mN, p < 0.05, t-test). Stents were implanted into six coronary artery bifurcations each using the single-stent crossover technique without side branch strut dilatation. Outcomes were examined after 28 days.Results: Implantation of both stents significantly increased site angulation (Multi-link 8: 148° ± 8° to 172° ± 2°, p < 0.05, paired t-test; Kaname: 152° ± 5° to 164° ± 4°, p < 0.05, paired t-test), but the change tended to be greater after Multi-link 8 stent implantation (24° ± 15° vs 11° ± 7°, p = 0.1, t-test), suggesting greater straightening of the bifurcation. The Multi-link 8 stent induced greater neointimal thickness than the Kaname stent (0.53 ± 0.3 mm vs 0.26 ± 0.1 mm, p < 0.05, t-test). The distribution of neointimal hyperplasia following stent implantation as revealed by longitudinal histopathology matched the distribution of WSS simulated using computational fluid dynamics (CFD). The endothelium at low WSS areas exhibited aberrant cell morphology and leukocyte adhesion. A CFD model of a curved bifurcation suggested that the region of low WSS is expanded by artery straightening.Conclusion: In bifurcated lesions, stent flexibility influences not only mechanical stress on the artery but also WSS, which may induce local neointimal hyperplasia.Keywords: bifurcation, stent flexibility, wall shear stress, neointimal hyperplasia